Efektivitas program kelas ibu balita pada penanganan stunting - Iin sangoi; Herlina Jusuf; Vidya Hadju (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Stunting is a serious child health problem in Indonesia, including in Gorontalo Province. Efforts to address stunting have been implemented through various programs, one of which is the mothers and Toddlers Class. Purpose: To describe the effectiveness of the mothers and Toddlers Class program in addressing stunting. Method: This study is a qualitative study. Key informants were the people in charge of the mothers and Toddlers Class program and cadres. Six supporting informants were participants in the mothers and Toddlers Class. This study was conducted at the Telaga Biru Community Health Center in May 2025. Results: The study shows that the program has been implemented routinely and integrated with integrated health post (Posyandu) activities, with indicators including goal achievement (timeframe, targets, and legal basis), integration (procedures and socialization processes), and adaptation (improved capacity and infrastructure). Conclusion: Although the program has shown a positive impact on improving maternal knowledge and behavior, obstacles remain, such as low understanding of stunting in some communities and limited active participation. The Mother and Toddler Class Program is quite effective in supporting stunting management, although there has been improvement in community understanding and involvement.